Building native web components : front-end development with Polymer and Vue.js - Rojas, Carlos (Apress, 2021)
Start developing single-page applications (SPAs) with modern architecture. This book shows you how to create, design, and publish native web components, ultimately allowing you to piece together those elements in a modern JavaScript framework. Building Native Web Components dives right in and gets you started building your first web component. You'll be introduced to native web component design systems and frameworks and discuss component-driven development to understand its importance in large-scale companies. You'll then move on to building web components using templates and APIs, and custom event lifecycles. Techniques and best practices for moving data, customizing, and distributing components are also covered. Throughout, you'll develop a foundation to start using Polymer, Vue.js, and Firebase in your day-to-day work. Confidently apply modern patterns and develop workflows to build agnostic software pieces that can be reused in SPAs. Building Native Web Components is your guide to developing small and autonomous web components that are focused, independent, reusable, testable, and works with all JavaScript frameworks, modern browsers, and libraries. You will: Incorporate component-driven development (CDD) and design systems into your workflow Build apps with reusable UI components that are agnostic to JavaScript frameworks Utilize Polymer and Vue.js in your day-to-day work Publish your UI components in npm (Node Package Manager).